Bioscrubber treatment of exhaust air from intensive pig production: Case study in northern Germany at mild climate condition - Liu,F; Fiencke,C; Guo,J; Rieth,R; Cuhls,C; Dong,R; Pfeiffer,E (Engineering in Life Sciences, 2017)
Treatment by fieldscale bioscrubber of exhaust air, including ammonia (NH 3 ) and the greenhouse gases methane (CH 4 ), nitrous oxide (N 2 O), and carbon dioxide (CO 2 ), from 13 intensive pig production houses located in northern Germany were investigated in 2013 and 2015. NH 3 removal efficiencies varied between 35 and 100% with an overall average value of 79% under the NH 3 inlet fluctuations from 34 to 755 g d −1 m −3 in both 2013 and 2015. Results of the electron microscopic analyses demonstrated that the bacteria Nitrosomonas sp. and methanotrophs type I were the dominant NH 3 and CH 4 oxidizers, respectively. However, overall average removal efficiencies of CH 4 was approximately zero, which means CH 4 is hard to remove in bioscrubbers under normal operation. The pH of recirculation water in the bioscrubber varied from 6.1 to 8.1, and the bioscrubbers with low pH values (<7.0) had high NH 3 removal efficiencies (>79%). Electrical conductivity was commonly used to diagnose the bioscrubbers’ performance; in the present study, electrical conductivity presented a significant linear relationship with dissolved inorganic nitrogen, which indicates the performance stability of the 13 selected bioscrubbers.